İsmail Hakkı Bursevi and the politics of balance - Tabur, Merve. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2011., 2011)
This thesis examines the religio-political commentary of a late seventeenth and early eighteenth century Celveti sheikh, İsmail Hakkı Bursevi, who operated in the lands of the Ottoman Empire. The main focus is on the representation of political and spiritual authorities and Sufi-state relations in six texts composed by Bursevi in the early eighteenth century. The analysis of these narrative sources reveals that İsmail Hakkı Bursevi was one of the many commentators on what has been narrated as a post-Süleymanic decline in Ottoman historiography up to this day. As a follower of the twelfth century mystic Ibn ‘Arabi, Bursevi defined the reasons of decline and provided possible solutions to restore order within a religious discourse which fed from Sufi notions and concepts. Thus he formulated a Sufi interpretation of the decline paradigm. The estrangement of spiritual and political authorities, represented by the Sufi sheikh and the sultan respectively, formed the basis of his arguments. Furthermore, his views regarding the spiritual authority of the Sufi sheikh as the saint and the inheritor of the prophet reflect the ways in which the Sufi sheikh founded his legitimacy and situated himself vis-a-vis the Ottoman state. This thesis elaborates Bursevi’s political thought by contextualizing it not only within particular intellectual traditions but also within the historical realities of the period.
Keywords: Sufi literature, Turkish -- History and criticism.; Sufism -- Doctrines -- Early works to 1800.